Щодо використання відеоконференцзв’язку при перегляді судових рішень у касаційному порядку - Смирнов Максим Іванович; Смирнов Максим Иванович; Smirnov Maksim I. (My University, 2004)
The article considers legal procedure issues of implementing new information technologies in criminal process. The concept of «distance trial» - which provides for a possibility to apply video communication not only to particular actions but to entire criminal processes - should be adopted in both investigations and procedure. Application of video communication shortens the period of time needed for getting evidence or carrying out missions to be fulfilled abroad, cuts down international travel expenses, thus, minimizing the expected negative outcomes of a long criminal case process. Besides, video communication facilitates exercising the right to confrontation in interrogating a witness who is outside the country.
Смирнов М. І. Щодо використання відеоконференцзв’язку при перегляді судових рішень у касаційному порядку / М. І. Смирнов // Вісник Верховного Суду України. – 2004. - № 1 (41). – С. 38-40.
Keywords: відеоконференцзв’язок; інформаційні технології в судочинстві; міжнародне співробітництво; кримінальна юстиція; касаційний розгляд кримінальних справ; національний кримінальний процес; видеоконференцсвязь; информационные технологии в судопроизводстве; международное сотрудничество; уголовная юстиция; кассационное рассмотрение уголовных дел; национальный уголовный процесс; videoconferencing; information technology in legal proceedings; international cooperation; penal justice; cassation in the criminal cases; national criminal procedure